Tax Service Quality, Taxpayer Compliance, and Motor Vehicle Tax Revenue Performance at UPPD SAMSAT Sentani - Isbel Rumboirusi; Hasan Basri Umar; Transna Putra Urip (LPPM STIE KRAKATAU, 2024)
Purpose: This study examines the effect of tax service quality on taxpayer compliance and its implications for motor vehicle tax revenue performance at UPPD (Unit Pelaksana Pengelola Pendapatan Daerah) SAMSAT (Sistem Administrasi Manunggal Satu Atap) Sentani, and tests whether taxpayer compliance mediates the relationship between service quality and revenueperformance. Methodology: A quantitative approach was applied using a sample of 100 respondents drawn through stratified random sampling from 89,305 registered taxpayers, determined using the Slovin formula with a ten percent margin of error. Data were collected through a questionnaire and analyzed using descriptive statistics and path analysis with SPSS version 27, following validity, reliability, and classical assumption testing. Results: Tax service quality has a significant positive effect on taxpayer compliance and on revenue performance, while compliance itself does not significantly affect revenue performance. Service quality and compliance jointly affect revenue performance, and the indirect effect of service quality on revenue through compliance exceeds its direct effect. Conclusions: Quality service raises compliance, which in turn contributes to higher tax revenue, although revenue responds more directly to service quality and tariff policy than to compliance alone. Limitations: The study is cross-sectional, confined to one SAMSAT office, and omits variables such as awareness, sanctions, or taxpayers' economic condition. Contributions: The study offers integrated path-analytic evidence on how service quality, compliance, and revenue interact under Papua's newly implemented Opsen tax policy.